THE IMPACT OF FEMALE DIRECTORS, DIRECTOR DUALITY, AND FINANCIAL PERFORMANCE ON THE INDONESIAN BANKING BOARD OF DIRECTORS’ COMPENSATION - Herni Kurniawati; Yustina Peniyanti Jap (Graduate Program of Universitas Tarumanagara, 2026)
Over the past few decades, the topic of board of directors' compensation has drawn a lot of scholarly attention. It is believed that the compensation is appropriate in order to make employees happy and motivated to work for the company in order to achieve the goals of stakeholders. A number of factors, including the percentage of women on the board, the duality of members, and the bank's financial performance, affect how much compensation the board of directors receives. The purpose of this study is to demonstrate empirically how financial success, the presence of female directors, and director duality impact the salary that directors earn. The research sample consists of banking businesses from 2019 to 2023, and the research methodology is quantitative description utilizing annual report data. The eViews 12 software tool aids in this research. The findings of this study indicate that the number of female directors and the bank's financial success have an impact on the amount of compensation paid to directors; the former increases while the latter decreases. However, it has been demonstrated that the compensation of bank directors is unaffected by the duality of the board of directors.